Inter-Enterprise Arrears in a Post-Command Economy : Thoughts From a Romanian Perspective - Daianu, Daniel (IMF Working Papers; Working Paper, 1994)
The paper considers that strain is the main source of inter-enterprise arrears in post-command economies. Strain can be linked with the structure of the economy and the size of resource misallocation. Inter-enterprise arrears 'soften' markets and operate as a self-protecting device against the pressure for change. As temporary quasi-inside money, arrears fuel inflation. A paradox of policy credibility in undertaking structural adjustment is emphasized. Rising exports can be a possible side effect of arrears and a constraining factor: the size of the economy is seen as affecting the relationship between arrears and exports. An operational framework for containing arrears would Include: 'breaking up' structure; Imposing a disciplining 'straitjacket' on structure; industrial policy ('picking losers among losers') and targeted external assistance. Containing arrears can not be a one shot policy-drive; here one deals with a process that will overlap in time with the evolving environment.